2009
DOI: 10.1007/s12105-009-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Site Based Ploidy Analysis of Oral Premalignant Lesions

Abstract: The location of oral leukoplakia correlates strongly with the probability of finding dysplastic or malignant alterations at biopsy. It is well established that early detection can dramatically improve the 5-year survival rates for oral squamous cell carcinomas. Since aneuploidy is predictive of future conversion to malignancy, we hypothesized that dysplastic lesions from highrisk sites (floor of mouth, tongue and lips) would exhibit greater aneuploidy than low-risk sites (palate, gingiva and buccal mucosa). Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
3
22
0
1
Order By: Relevance
“…Different intraoral sites, particularly floor of mouth, ventrolateral tongue and soft palate complex, have been proposed as a high risk of OL malignant transformation (van der Waal, ). These sites exhibited a high frequency of aneuploidy and loss of heterozygosity (LOH) (Zhang et al , ; Islam et al , ; Castagnola et al , ). However, not always just OLs have been included in these studies, and prospective clinical studies are needed to confirm these findings.…”
Section: What Percentage Of Ols Transform Into Oscc?mentioning
confidence: 99%
“…Different intraoral sites, particularly floor of mouth, ventrolateral tongue and soft palate complex, have been proposed as a high risk of OL malignant transformation (van der Waal, ). These sites exhibited a high frequency of aneuploidy and loss of heterozygosity (LOH) (Zhang et al , ; Islam et al , ; Castagnola et al , ). However, not always just OLs have been included in these studies, and prospective clinical studies are needed to confirm these findings.…”
Section: What Percentage Of Ols Transform Into Oscc?mentioning
confidence: 99%
“…According to previous papers, the lateral tongue is reported to harbor many dysplasias or malignancies (5, 6). In a recent study, 85% of leukoplakia in the lateral/ventral tongue is reported to exhibit aneuploidy, which is recognized as one of the risk factors of malignant transformation: 50% occurring on the floor of the mouth, 44% in the soft palate, and 22% in the gingival (7).…”
Section: Introductionmentioning
confidence: 99%
“…Aneuploidy was found to be significantly and positively associated with the histologic grade of dysplasias (Saito et al , 1995; Pentenero et al , 2009; Donadini et al , 2010). Even mild dysplasias may show aneuploidy particularly if these are located on the tongue or floor of mouth (Islam et al , 2010). One study showed that aneuploid dysplasias were more likely to progress than diploid lesions (33% vs 11%, P = 0.01) and that aneuploid lesions transformed to OSCC within 5 years in 53% of cases vs 25% of diploid cases (Torres‐Rendon et al , 2009b).…”
Section: Aneuploidymentioning
confidence: 99%